Two-year clinical results following treatment of peri-implantitis lesions using a nanocrystalline hydroxyapatite or a natural bone mineral in combination with a collagen membrane - Frank Schwarz, Anton Sculean (Blackwell Synergy, 2008)
Objectives: The aim of the present case series was to evaluate the 2-year results obtained following treatment of peri-implantitis lesions using either a nanocrystalline hydroxyapatite (NHA) or a natural bone mineral in combination with a collagen membrane (NBM1CM). Material and Methods: Twenty-two patients suffering from moderate peri-implantitis (n522 intra-bony defects) were randomly treated with (i) access flap surgery (AFS) and the application of NHA, or with AFS and the application of NBM1CM. Clinical parameters were recorded at baseline and after 12, 18, and 24 months of non-submerged healing. Results: Two patients from the NHA group were excluded from the study due to severe pus formation at 12 months. At 24 months, both groups revealed clinically important probing depth (PD) reductions (NHA: 1.5 0.6 mm; NBM1CM: 2.4 0.8 mm) and clinical attachment level (CAL) gains (NHA: 1.0 0.4 mm; NBM1CM: 2.0 0.8 mm). However, these clinical improvements seemed to be better in the NBM1CM group (difference between groups: PD reduction: 0.9 0.2 mm; CAL gain: 1.0 0.3 mm). Conclusion: Both treatment procedures have shown efficacy over a period of 24 months, however, the application of NBM1CM may result in an improved outcome of healing.